Questionando o papel dos especialistas em educação frente à democratização da gestão - Garcia, Carlos Alberto Xavier (2006)
In this work, the author investigates, within the school management field, the technical specialists who incorporate the school s directive staff (school administrator, educational supervisor and advisor), positions designed to scholar organizations after the fabric working division. The main aim is to question the role of specialists towards the management democratization. To do so, the pedagogic proposal and the practices observed in public school through the community s testimonies represent a remarkable importance to the analysis presented by the author, once the pedagogic work comprises these distinguished positions to the collective actions coordination in the scholar organization. This evidence reinforces the idea of overcoming the work division inside the school, with the historical partition, still remaining, between the ones who plan and the ones who act. Both bibliographic and field research, in a qualitative profile, attempted to find out the origin of education specialists function, their incursion into the Brazilian Educational system through school management work, their relevance to management providing a following overcome to the sectors partition and also to determine the space and role of specialists in the management democratization. It was intended to develop a documentary analysis, interviews and questionnaires within the scholar community that are part of the 19th CRE (Regional Educational Coordination) in the São Gabriel County, which assist elementary education in the east, west and central regions, counting with scholars from different social and age levels. Although this position is still considered of importance, renowned by most community members, it is understood that this position deserves a redefinition. There is a need for a continued development to supervisors, principals and educational advisors in order to be articulators in the democratic management. In that way, it could be possible for the school to accomplish its autonomy.